ETIKA BERKOMUNIKASI PERSPEKTIF HADIS (Dalam Kutub at-Tis’ah) - Darussalam Darussalam; Neng Lutfi Maspupah (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
Human nature is born in a sacred condition (fitrah), and one of its forms of purity (fitrah) is communication. Good communication is effective and efficient communication so that it can deliver to success also gives problems for everyone. In certain conditions, communication can also have a bad impact if it is not controlled so that it can cause hatred, hostility, fights can even cause death due to communication that is not ethical, excessive and uncontrolled. Therefore, ethics is certainly an important and indispensable part of communication. In this study the author aims to identify the ethics of communication based on the hadith of the Prophet Muhammad. The method in this study uses the library method (Library Research), which is a data collection technique by conducting a study of books, journals, and other literature that have a relationship with related problems.